EKSPLORASI PERILAKU KEPEMIMPINAN PUSKESMAS LIYA KECAMATAN WANGI-WANGI SELATAN KABUPATEN WAKATOBI - Muhamad Raflianto Ode; Murdjani Kamaluddin; Laode Asfahyadin Aliddin; Asrip Putera; Nurul Ittaqullah (Jurusan Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Halu Oleo, 2022)
This study aims to describe leadership behavior at the Liya Public Health Center, Wangi-Wangi Selatan District, Wakatobi Regency. Qualitative descriptive approach was used in conducting this research and used data collection methods by observation, interviews, and documentation. The technique used in data analysis is to organize the data , break it down into units, synthesize, arrange into patterns, choose which ones are important and what will be studied, and draw conclusions. The results of this study indicate that Liya Health Center leaders are leaders who have leadership behavior oriented to achievement. This is in accordance with the indicators of leadership behavior that uses the theory indicator of the path of road-goal (Path-Goal Theory) developed by Robert House which consists of: directive leadership behavior, supportive leadership behavior, leadership behavior participatory, and leadership behavior oriented towards achievement.